AGE-RELATED CHARACTERISTICS OF FOREIGN LANGUAGE TEACHING IN PRIMARY GRADES (Web of Teachers: Inderscience Research, 2025)
This article is devoted to modern methods and approaches to teaching English in primary grades, their impact on the learning process and student results. The article analyzes the age-related characteristics of the communicative approach, integration of modern technologies, individual methods and methods for developing intercultural communication competence in English lessons, and considers the results.